Agronomic performance of irrigated rice hybrids on the Western border of Rio Grande do Sul - Follmann, Diego Nicolau; Farenzena , João; Schlösser, Onássis; Santos, Emilso Damm dos; Zanon , Alencar Junior; Nardino , Maicon (Scientia Agraria Paranaensis, 2022)
Rice crops are essential in World Food Security. Brazil is the largest rice producer outside Asia, with increasing research investments, including using hybrid cultivars with high productive potential. The objectives of this study were to compare the agronomic performance of three cultivars of irrigated rice, two hybrids and one conventional, in the municipality of Uruguaiana, on the western border of Rio Grande do Sul. The experiment was conducted in the 2017/2018 crop with four replicates in a completely randomized design. The three treatments consisted of the cultivar Guri Inta CL and the hybrids Titan CL and Lexus CL. Morphological characters (plant stature, panicle length, grain length, grain width, grain appearance) and yield components (weight of one thousand grains, number of grains per panicle, number of sterile grains per panicle, plant population, whole grain yield) were evaluated. The statistical analyzer S-21 was used to determine the variables of appearance and grain size. The agronomic performance of hybrid cultivars presents lower quality for whole grain yield and the percentage of chalky grains. The morphological characteristics of the plant indicate that hybrid cultivars compensate for the lower initial population by producing more branches and larger panicles without compromising grain yield. Grain yield showed no significant difference, demonstrating the lack of economic viability in this agricultural year for cultivating rice hybrids in Uruguaiana. Significant correlations were verified between the productive characteristics and rice grain quality, showing the relationships between grain productivity and rice grain quality.